IoT - development of a home automation system - Goh, Benjamin Zongye (Nanyang Technological University, 2023)
In the last decade advancement in semiconductors and wireless networking have made the Internet of Things very practical and one of the largest developing technologies of the new millennium. It has use cases in many sectors such as healthcare, logistics, farming and in the focus of this paper, home automation. Home automation is mainly marketed towards consumers who want to ease and simplify their day to day lives, using technology to work on the mundane or non-easily accessible tasks for them. This paper aims to teach readers how they can develop their own smart home system using low cost microcontrollers and widely available software tools